Investigation and comparative analysis of materials, efficiency, and design in microbial electrolysis cells for biomethane production - Deb, Nibedita; Rahman, Tawfikur; Alam, Md. Zahangir; Jami, Mohammed Saedi; Miah, Md Shohidullah (Iranian Research Organization for Science and Technology, 2025)
The escalating global demand for energy and the imperative to address greenhouse gas emissions have spurred the exploration of alternative energy sources. Microbial Electrolysis Cells (MECs) have emerged as a promising technology, converting organic compounds into electrical energy and hydrogen gas. A recent breakthrough, namely a hybrid (H-MEC) system, integrates electromethanogenesis to convert CO2 to methane, offering a novel avenue for efficiently harnessing renewable energy and mitigating emissions. This paper underscores the significance of optimizing the design, materials, and operational strategies to enhance the scalability and efficiency of MECbased electromethanogenesis. Traditional anaerobic digestion processes, converting biomass residues and food waste into hydrocarbon bioenergy, are being redefined through the integration of H-MECs. This integration presents opportunities for improved effluent treatment, heightened methane production, and the generation of valuable compounds. Recent studies reveal the remarkable ability of ionic conductivity and electrochemical reactions within bacteria to synthesize hydrocarbons, emphasizing factors such as microbes, biofilm development, substrates, and electrode surfaces for amplified methane yields. H-MECs demonstrate exceptional versatility in consuming diverse substances, notably untreated food waste, positioning them as potent microbial biocatalysts. The diligent exploration of this domain has given rise to various H-MEC technologies for hydrogen generation and carbon dioxide reduction. This review delves into the mechanisms and methodologies of H-MECs for electromethanogenesis through varied biochemical reactions, shedding light on single or double-chambered MECs